Il carcere al femminile: caratteristiche, sviluppi e possibilità - Dario, Claudia; Giampà, Alessio (Il sogno della farfalla, 2022)
Worldwide, an increasing number of women are secluded in jails. Despite this, few studies have focused on their living condition in the restrictive prison’s environment and on the potential effect on their mental health. On a global scale, the current detention model is conceived around the idea of male detainees. Consequently, with regards to women there is a complete lack of attention towards possible social and cultural differences and preexistent psychiatric pathologies. Female population currently secluded in Italian jails includes a considerably high percentage of women suffering from psychiatric condition or affected by substance abuse. This reality should be object of further investigation and research in the psychiatric field. With this regard, this article presents a clinical case which elucidates the complexity of the treatments needed to guarantee mental health in the penitentiary context. Finally, the authors paper question the efficacy of preventive measures prior to detention and the possibility to humanize the penitentiary environment.